Intramolecular aryl-aryl coupling: Via C-F bond activation tolerant towards C-I functionality - Steiner, Ann-Kristin; Feofanov, Mikhail; Amsharov, Konstantin (Chemical Communications, 2020)
Herein we report a transition-metal free activation of a particularly stable aromatic carbon-fluorine bond allowing intramolecular aryl-aryl coupling which is orthogonal to carbon-iodine functionality.
CRIS-Team Scopus Importer:2020-12-04